Impact of business strategy aligned with information technologies on the prof-itability of Mypes in Trujillo (SCIÉNDO INGENIUM, 2025)
The objective of the research was to identify the business strategies linked to information technologies that MSMEs use to improve their profitability. The methodology involved selecting a sample stratified by economic sector. The dimensions of the research variable were information technologies linked to Marketing, Digitalization of processes and Training-Coaching and work of Human Resources. The existence of variables that interfere in the administrative process is business informality and one of the great benefits is the improvement of the quality of the products. Concluding that the success of MSMEs is in the use of balanced technological resources in the areas of the company.
Keywords: Business; small business; business administration; information technology; communication technology